Enhancing Physical Appearance On Self Esteem: The Intensity Of Learning As A Moderation - Conny Tjandra Rahardja (Akademi Akuntansi YKPN Yogyakarta, 2022)
This study investigated the effect of physical appearance on self-esteem with the intensity of learning via media as a moderating variable. The data were processed by regression analysis to examine the effect of physical appearance on self-esteem without involving moderation. The data were also tested with sub-group analysis to test whether the intensity of learning via media as a moderating variable was able to strengthen the effect of physical appearance on self-esteem. The test results without moderation denote that physical appearance has a positive effect on self-esteem. The results of the sub-group analysis indicate that the effect of physical appearance on self-esteem will be stronger for respondents who have the intensity of learning to exercise their faces and bodies regularly. Physical appearance positively and significantly affects self-esteem in respondents who have routine learning intensity. However, physical appearance does not affect self-esteem in respondents who have low learning intensity and are not routine. There are 144 respondents who joined in this research.